2014
DOI: 10.1590/0102-311x00116313
|View full text |Cite
|
Sign up to set email alerts
|

Melhoria da qualidade das informações sobre tuberculose a partir do relacionamento entre bases de dados

Abstract: O objetivo deste trabalho foi verificar a melhoria da qualidade das informações sobre a tuberculose (TB), após a vinculação de registros e a correção do encerramento por meio do linkage probabilístico do Sistema de Informações de Agravos de Notificação (SINAN) com o Sistema de Informações sobre Mortalidade (SIM). Para a vinculação de registros foi realizado o linkage entre os registros do SINAN do Brasil, anos 2008 e 2009, com o objetivo de excluir as notificações não removidas pelas rotinas do SINAN realizada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
22

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 13 publications
0
26
0
22
Order By: Relevance
“…Furthermore, a study conducted in the Brazilian urban centers with the greatest TB load revealed that between 2001 and 2006, microscopy variables in the 2 nd , 4 th and 6 th months had the lowest proportions of entries in the TB information system 31 . In 2008, the states of Acre, Roraima, São Paulo and Mato Grosso do Sul presented good results in terms of linkage and the analysis of record duplication 16 . These findings, though for other indicators, corroborate the good quality found in this study of the Acre and Roraima information systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study conducted in the Brazilian urban centers with the greatest TB load revealed that between 2001 and 2006, microscopy variables in the 2 nd , 4 th and 6 th months had the lowest proportions of entries in the TB information system 31 . In 2008, the states of Acre, Roraima, São Paulo and Mato Grosso do Sul presented good results in terms of linkage and the analysis of record duplication 16 . These findings, though for other indicators, corroborate the good quality found in this study of the Acre and Roraima information systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies, usually only one of the attributes proposed by the CDC (2001) 15 , data quality [16][17][18][19] was employed in calculations, they took place in small localities 12,[20][21][22] or in specific states 13,14,23 . The most extensive study analyzed the quality of TB surveillance in Brazilian municipalities between 2001 and 2003 10 .…”
mentioning
confidence: 99%
“…It is still made difficult to estimate the number of cases that are lost in the system, but it is highly relevant to recover these missing data so that the routine retrieval of data from different sources of information used by TCPs can minimize the occurrence of the problem. 19 When asked about the possibility of choosing a service to alleviate the burden of poverty during TB treatment, both patients preferred to receive the "food stamps", referring to this item as "Bolsa Família", a Brazilian government program that provides financial aid to poor families in the country. Only in the municipality of Vitoria does this incentive exist to improve adherence to treatment, as well as a social voucher to cover the costs of transportation of the patient to the unit during visits, and which is assured by a Municipal Law, No.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of information from the municipality of origin in SINAN, SITETB and SIM also prevent deeper analyses about migration. In other investigations 11,41 , the collection of complementary data in the TB Record Book and in the Laboratory Record Book contributed with monitoring and the feedback of systems.…”
Section: Discussionmentioning
confidence: 99%